Effect of serum protein on cell internalization of silica nanoparticles. (28th January 2022) - Choi, Jae Won; Kim, In Young; Kwak, Minjeong; Kim, Jaeseok; Yoon, Sohee; Jang, Hyun Jun; Lee, Tae Geol; Heo, Min Beom
Abstract: Nanomaterials such as silica (SiO2 ) nanoparticles (NPs) are used in various fields owing to their unique properties, especially in biomedical applications. It has been reported that these particles induce different kinds of toxicity in various cells; therefore, it is very important to perform multifaceted analyses for accurate nanotoxicity evaluation. Most existing studies have primarily been conducted in the presence of serum, which could agglutinate SiO2 NPs, making it difficult to maintain the original size of the NPs and potentially causing errors in toxicity evaluation. Therefore, this study investigated the effects of serum proteins on the toxicity and internalization of SiO2 NPs. The toxicity of three types of monodisperse SiO2 NPs was examined in a serum‐free environment using human liver cancer (HepG2) cells and lung cancer (A549) cells. It was observed that the toxicity is significantly reduced by protein corona formation. The size‐dependent effect of SiO2 NPs on apoptosis and necrosis was also investigated, and it was observed that both apoptosis and necrosis occur under serum‐free or low‐concentration serum conditions after exposure of the cell lines to SiO2 NPs. These findings suggest that serum proteins are among the most important factors to be considered while evaluating the cytotoxicity of nanomaterials.